Vehicular mediated emissions of polycyclic aromatic hydrocarbons in roadside soils of Shanghai - Qi Huang; Min Xu; Yingying Zhu; Xin Li; Jiadong Xu; Xiaojian Li; Ying Lu (Scientific Reports)
Abstract This study evaluates the impact of vehicular emissions on polycyclic aromatic hydrocarbons (PAHs) in roadside soils in Shanghai during the COVID-19 lockdown period. Soil samples from roadside lawns were collected, with PAH concentrations ranging from 153 to 5639 ng g−1. A significant reduction in PAH levels compared to their pre-COVID-19 levels (Kruskal–Wallis H test, p < 0.05) was observed in surface soil samples, highlighting the contribution of traffic and coal combustion to urban pollution. Source identification, using molecular diagnostic ratios and principal component analysis, revealed that vehicular emissions were the primary contributors to PAHs in Shanghai’s roadside soils. The toxic equivalent quantity for benzo[a]pyrene concentrations in the soil samples was associated with these sources. The incremental lifetime cancer risk model indicated that adult exposure to PAHs in the soil posed health risks greater than 10−6 but lower than 10−4, suggesting a low-risk level. These findings suggest that targeted measures in the transportation sector could improve urban soil quality and reduce associated health risks.